Antimicrobial, Antiproliferative and Antioxidant Activities of Eethanolic, Ethyl Acetate and Petroleum Ether Extracts of PsidiumGuajava Leaves - Adeel Zafar , Khalid Mahmood , Muhammad Naim Ashraf , Farheen Ansari , Sana Javaid Awan , Kanza Tariq (Journal of Rawalpindi Medical College, 2016)
Background: To determine the antimicrobial, antiproliferative and antioxidant activities of ethanolic, ethyl acetate and petroleum ether extracts of Psidiumguajava leaves. Methods: The antimicrobial activity was assessed using disc diffusion method on Staphylococcus aureus, Bacillus cereus, Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli and Salmonella typhi. The anti-proliferative activity was determined on HeLa cell lines. The anti-proliferative activity was assessed using MTT assay while antioxidant activity was determined using catalase and superoxide dismutase (SOD) assays. Results: The MTT results indicate that ethyl acetate and petroleum ether extracts have significantly inhibited the proliferation of HeLa cells as compared to the control. Antioxidant assays showed that catalase activity was insignificant for all extracts however the SOD activity was significant. All the extracts showed inhibitory zones against B. cereus while only ethanolic extract of P. guajava leaves was active against S. aureus. Conclusion: Psidiumguajava plant leaves extracts can be used as antiproliferative agent against HeLa cell line